Measuring the factors affecting awareness in renewing business registration certificates (BRC) among entrepreneurs in Penang, Malaysia / Muhammad Abu Hanifah Ahmad Sohaimi, Azyyati Anuar and Nur Zainie Abd Hamid - Ahmad Sohaimi, Muhammad Abu Hanifah; Anuar, Azyyati; Abd Hamid, Nur Zainie (Research Management Centre (RMC), 2023)
In the fast-paced and ever-changing business landscape, maintaining precise and current business registration is crucial for entrepreneurs to ensure legal adherence and capitalise on growth opportunities. This cross-sectional study meticulously assesses the level of awareness among entrepreneurs in Penang regarding the renewal of their business registration certificates (BRC). Data were gathered from 384 participants representing diverse business sectors through an online questionnaire. The study employed descriptive statistics and the Kruskal-Wallis test to compare awareness scores among sectors. The findings unveil distinct levels of awareness, with retail entrepreneurs exhibiting the highest median awareness score. This study underscores the imperative need for targeted educational and outreach endeavours, orchestrated by regulatory bodies and business associations to empower entrepreneurs with comprehensive knowledge on compliance obligations and the potential ramifications of non-compliance. The insights furnish vital theoretical implications, elucidating sector specific disparities in awareness and advocating for robust enforcement mechanisms to uphold compliance standards. Furthermore, from a managerial standpoint, the study emphasizes the importance of prioritizing educational initiatives to elevate awareness levels, streamlining the registration and renewal process, and nurturing a culture of informed vigilance among business owners regarding regulatory requirements. By implementing such measures, entrepreneurs can mitigate legal and financial risks, fostering an environment conducive to entrepreneurial growth. Consequently, the study's valuable contributions support the thriving small businesses in Penang, paving the way for future research on additional factors that shape awareness and compliance with regulatory mandates over time.